Procalcitonin and Pentraxin-3: Current biomarkers in inflammation in white coat hypertension - Yavuzer, H; Cengiz, M; Yavuzer, S; Rıza Altıparmak, M; Korkmazer, B; Balci, H; Yaldıran, A L; Uzun, H (Journal of human hypertension, 2016)
An association has been described between inflammation and the progression of hypertension (HT) and is shown with several biochemical parameters. Our aim was to examine the distribution of the serum procalcitonin (PCT), pentraxin (PTX)-3 and interleukin (IL)-33 levels and their relationship with carotid intima–media thickness (CIMT) in subjects with white coat HT (WCH), HT and normotension (NT) groups. Thirty-three patients with HT, 33 patients with WCH and 33 healthy subjects were enrolled in this study. PCT, PTX-3 and C-reactive protein (CRP) levels significantly increased in the HT group compared with the NT group. In addition, PCT and CRP levels were significantly higher in the WCH group than in the NT group. CIMT measurements were significantly higher in the WCH and HT groups than in the NT group. In the HT and WCH groups, there were significant positive correlations between PTX-3, PCT and CRP. In the WCH group, PTX-3 and PCT levels were significantly positively correlated with CIMT. PCT had area under the curve value of 0.817 which demonstrates its sufficiency to distinguish WCH from NT individuals. Our results suggest that in subjects with WCH and HT, which are characterized by increased cardiovascular risk, PTX-3 and PCT levels in the HT group and PCT levels in the WCH group are significantly and consistently higher than normotensives. Systemic inflammation moderately occurs in the WCH and HT groups. PCT monitoring may be a useful biomarker in inflammation related to atherosclerosis and early stage HT.